Intricately carved Makara-Torana - Temples of India Project Team (Jio Institute, 2024)
The mukhamandapa (front porch) of the Ghateshwar Temple has an entry through an intricately carved makara-torana (ornamental arch adorned with intricate carvings of mythical crocodile creatures). The torana (ornamental arch) shows makara (crocodile) on each end. These makaras are being attacked by knights with a sword in their mouth. The floral bands emitting from the mouths of the makaras form a pointed arch, above which musicians are shown seated, playing musical instruments, and singing. At the apex, a kirtimukha (face of glory) flanked by two flute players is depicted.